PROFESSIONALS OF LAW IN EDUCATION: CONSIDERATIONS ON THE SUBJECTIVE PUBLIC LAW - Assumpcao Bertuol, Patricia de Oliveira; Silva, Marta Leandro da [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This article deals with the normative trajectory of the constitutional right to a quality education, in the interdisciplinary perspective of Education and Law. It is linked to the activities of Master's Research in School of Education by Unesp - FCLAr and to the interdisciplinary studies of the Research Group on Educational Public Policies in Brazil, presented orally in the XII EIDE - Ibero-American Meeting of Education in Alcala in Spain. On methodological basis of qualitative research in education articulated to the hypothetical deductive methodology and argumentative-dialectical juridical analysis with emphasis on documental research with legal basis. It was prioritized to address the Brazilian Constitution of 1988 (CF), the Statute of the Child and Adolescent (ECA) and the Law of Basic Guidelines of Education - Law 9.394/96 (LDB). It is worth noting the social relevance of this issue, it was approached the importance in the training of legal professionals iterated on the subject for the effective realization of this subjective public right and the quality indicators for the community.
Keywords: Constitutional right to education; Law professionals; Educational policies